Vox populi or vox masculini? Populism and gender in Northern Europe and South America - Mudde, Cas; Kaltwasser, Cristóbal Rovira (Patterns of prejudice, 2015)
Conceptually, populism has no specific relationship to gender; in fact, gender differences, like all other differences within 'the people', are considered secondary, if not irrelevant, to populist politics. Yet populist actors do not operate in a cultural or ideological vacuum. So perhaps it is the national culture and broader ideology used by populists that determine their gender position. To explore this argument, we compare prototypical cases of contemporary populist forces in two regions: the Dutch Partij voor de Vrijheid (PVV, Party for Freedom) and the Dansk Folkeparti (DF, Danish People's Party) in Northern Europe, and the Partido Socialista Unido de Venezuela (PSUV, United Socialist Party of Venezuela) and the Bolivian Movimiento al Socialismo (MAS, Movement for Socialism) in South America. Populists in Northern Europe are predominantly right-wing, yet mobilize within highly emancipated societies, while populists in South America are mainly left-wing and mobilize in strongly patriarchal societies. Our analysis provides a somewhat muddled picture. Although populists do not necessarily have a clear view on gender issues, the latter are clearly influenced by ideology and region. While left-wing populists tend to be relatively progressive within their traditional South American context, right-wing populists mainly defend the status quo in their progressive Northern European context. However, in absolute terms, the relatively high level of gender equality already achieved in Northern Europe is at least as advanced as the one proposed by the populists in South America.